About the application of the Linnaean name Plantago latifolia (Plantaginaceae) - Iamonico, Duilio; Fortini, Paola; Di Pietro, Romeo (Phytotaxa, 2019)
Plantago Linnaeus (1753: 112) (Plantaginaceae) is a genus including 200–250 species distributed throughout the temperate zone and the high-elevation tropical regions (Rahn 1996, Rønsted et al. 2002).